I got this when Im suppose to be solving for x
$\displaystyle b(\frac{-2a^2}{x^3}-\frac{a}{x^2})=0$
but i dont see how it can me turned into this -its from an example the book
$\displaystyle -2a^2+ax=0$
$\displaystyle b\left(\frac{-2a^2}{x^3}-\frac{a}{x^2}\right)=0\implies b\left(\frac{-2a^2}{x^3}-\frac{ax}{x^3}\right)=0$ $\displaystyle \implies b\left(\frac{-2a^2-ax}{x^3}\right)=0\implies -2a^2-ax=0$
I'm not sure where its getting $\displaystyle -2a^2{\color{red}+}ax=0$, unless there is a typo somewhere in what you posted.